Mobility in the Urban Labor Market: A Panel Data Analysis for Mexico - Xiaodong Gong; Arthur van Soest; Elizabeth Villagomez (Institute for the Study of Labor (IZA), 2000)
We analyze mobility in urban Mexico between three labor market states: working in the formal sector, working in the informal sector, and not working. We use a dynamic multinomial logit panel data model with random effects, explaining the labor market state of each individual during each time period. The data is drawn from Mexico ?s Urban Employment Survey, a quarterly household survey for urban Mexico. Two separate five-wave panels are used: the first covering a period of rapid economic growth (1992 ?1993), the second a period of recession after the Peso crisis (1994 ?1995). Our main results are in line with the theory that formal sector jobs are superior to informal sector jobs and that working in the informal sector is a temporary state for those who cannot find a formal sector job and cannot afford not to work. Entry and exit rates for the formal sector are lower than for the informal sector. The probability of formal sector employment strongly increases with education level. For men, it is easier to enter the formal sector from the nonworking state than from the informal sector. The probability of working in the informal sector decreases with the level of income of other family members, while the probability of not working increases with it.
Keywords: R23; C23; C25; J60; 330; Informal sector work; mobility; panel data; Mexico; Arbeitsmobilität; Städtischer Arbeitsmarkt; Informeller Sektor; Dualökonomie; Schätzung; Mexiko